Strategi Komunikasi Pariwisata Berbasis Penghijauan Eks-Lokalisasi Desa Kedung Banteng Menjadi Agrowisata Kebun Kelengkeng - Dafiyatur Rurojifah; Nafiah Nafiah; Khoirul Fathoni (Social Science Academic, 2025)
Kedung Banteng ex-localization village is currently in the process of positive and sustainable transformation by adopting the concept of greening towards longan orchard agrotourism. Various kinds of efforts are made to support the development of longan garden agro-tourism. Tourism communication strategies based on land greening have been carried out by community groups and also the village government. The development of agritourism will not only change the negative public image but also provide new economic opportunities and introduce the concept of sustainability in tourism management. This research aims to analyze and understand tourism communication strategies in the context of developing greening-based agritourism in Kedung Banteng Village. Data collection in this study was through observation, interviews, and documentation. This research is expected to provide insights for the government, destination managers, stakeholders and also the community to formulate a sustainable and more effective communication strategy. The results of this study are, greening-based tourism communication implemented in Kedung Banteng village has become an effective longan garden agrotourism to use the land as a socio-economic center for Kedung Banteng village, but there is a less effective communication process that goes along with the development of longan garden agro-tourism. There needs to be a significant evaluation and improvement to support the development of longan garden agrotourism.